2012
DOI: 10.1167/iovs.11-8232
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatic Effect of CXCR3 Expressed on Choroidal Neovascularization

Abstract: These results suggested that CXCR3 expressed on CNV could have an angiostatic effect on it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…We also found corneal neovascularization was dramatically decreased after topical administration of IP-10 protein. Fujimura et al 34 reported that IP-10/ CXCR3 could inhibit choroidal neovascularization by introvitroneally injecting anti-IP-10/CXCR3 neutralizing antibodies and they also found by real-time PCR that gene expressions of MCP-1 and VEGF were increased in CXCR3 KO mice. Consistently, we found that IP-10 inhibited corneal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found corneal neovascularization was dramatically decreased after topical administration of IP-10 protein. Fujimura et al 34 reported that IP-10/ CXCR3 could inhibit choroidal neovascularization by introvitroneally injecting anti-IP-10/CXCR3 neutralizing antibodies and they also found by real-time PCR that gene expressions of MCP-1 and VEGF were increased in CXCR3 KO mice. Consistently, we found that IP-10 inhibited corneal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…31 In estrogen receptor positive (ER+) mammary tumors, CXCL10 inhibits vascular endothelial growth factor (VEGF) levels to reduce the tumor burden. 32 The CXCR3-IP-10 axis plays a critical role in the development of tumor neovascularization and some ocular neovascularization such as choroidal neovascularization, [33][34][35] but its effects on corneal neovascularization are less clear. To further address the role of IP-10 signaling in ocular neovascularization, alkaliinduced CrNV was detected in IP-10-treated mice and was compared to vehicle-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…Mo et al [16] demonstrated that IP-10 expression was increased in the RPE in human donor eyes with early or advanced AMD. Using microarray analysis and real-time RT-PCR, Fujimura et al [29] demonstrated that CXCR3 and IP-10, but not monokine induced by interferon-γ and interferon-inducible T-cell α-chemoattractant, were elevated in RPE-choroid fractions in eyes from a laser-induced CNV mouse model compared with control eyes. They also reported that laser-induced CNV was significantly greater in CXCR3-deficient mice compared with wild-type mice, and intravitreal injection of IP-10 neutral antibody exacerbated CNV in a mouse model [29].…”
Section: Discussionmentioning
confidence: 99%
“…Using microarray analysis and real-time RT-PCR, Fujimura et al [29] demonstrated that CXCR3 and IP-10, but not monokine induced by interferon-γ and interferon-inducible T-cell α-chemoattractant, were elevated in RPE-choroid fractions in eyes from a laser-induced CNV mouse model compared with control eyes. They also reported that laser-induced CNV was significantly greater in CXCR3-deficient mice compared with wild-type mice, and intravitreal injection of IP-10 neutral antibody exacerbated CNV in a mouse model [29]. They speculated that exogenous administration of IP-10 could not attenuate CNV because endogenous IP-10 might be upregulated to saturation level after laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The current study investigated the association of PVD and the concentration of VEGF in the aqueous humour using ELISA. Furthermore, among the cytokines that have been shown to be associated with AMD,16 concentrations of the following cytokines in the aqueous humour were also determined using a multiplex cytokine assay; interferon-inducible protein 10 (IP-10), monocyte chemoattractant protein-1 (MCP-1), matrix metalloproteinase 9 (MMP-9), interleukin-6 (IL-6), interleukin-10 (IL-10), C-X-C motif chemokine ligand 1 (CXCL1), C-X-C motif chemokine ligand 12 (CXCL12), C-X-C motif chemokine ligand 13 (CXCL13), and C-C motif chemokine ligand 11 (CCL11).…”
Section: Introductionmentioning
confidence: 99%